Diet and Headache: Part 1. Issue 9 (October 2016) - Martin, Vincent T.; Vij, Brinder
Abstract : Background: The role of diet in the management of the headache patient is a controversial topic in the headache field. Objectives: To review the evidence supporting the hypothesis that specific foods or ingredients within foods and beverages trigger attacks of headache and/or migraine and to discuss the use of elimination diets in the prevention of headache disorders Methods: This represents part 1 of a narrative review of the role of diet in the prevention of migraine and other headache disorders. A PubMed search was performed with the following search terms: "monosodium glutamate, " "caffeine, " "aspartame, " "sucralose, " "histamine intolerance syndrome, " "tyramine, " "alcohol, " "chocolate, " "nitrites, " "IgG elimination diets, " and "gluten." Each of these search terms was then cross‐referenced with "headache" and "migraine" to identify relevant studies. Only studies that were written in English were included in this review. Results: Caffeine withdrawal and administration of MSG (dissolved in liquid) has the strongest evidence for triggering attacks of headache as evidenced by multiple positive provocation studies. Aspartame has conflicting evidence with two positive and two negative provocation studies. Observational studies provide modest evidence that gluten‐ and histamine‐containing foods as well as alcohol may precipitate headaches in subgroups of patients. Two of three randomized controlled trials reported that an elimination diet of IgG positive foods significantly decreased frequency of headache/migraine during the treatment as compared to baseline time period. Conclusions: Certain foods, beverages, and ingredients within foods may trigger attacks of headache and/or migraine in susceptible individuals. Elimination diets can prevent headaches in subgroups of persons with headache disorders.